Gestion de la décroissance et reproduction institutionnelle à I'ONUDI - Holly, Daniel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
This article explores the relationship between environmental changes and the reform process at the United Nations Industrial Development Organization (UNIDO). The basic question it seeks to answer is : how does an organization self-produce in conditions of intense environmental change ? International organizations, while carrying out their mission, are constantly called upon to take notice of changes in their environment and to make accordingly whatever adjustment is required. This adaptive process serves two main purposes : first, to facilitate the pursuit and attainment of the objectives of the organization and, second, to help the organization self-produce, for international organizations like any other social System self-produce through the action it exercises on it self. The reform process undertaken at UNIDO beginning in the late 80s clearly bears out that contention. It sheds light on the conditions and difficulties that surround the undergoing reform process at the United nations.